Peran Ekstrakulikuler Dalam Meningkatkan Kompetensi Sosial Anak Usia Dini - Mujahidah, Atika (Jurnal PAUD: Kajian Teori dan Praktik Pendidikan Anak Usia Dini, 2023)
Education is a conscious effort to create something hereditary and cultural from one generation to the next, forming a teaching model for previous generations. Educational institutions have the mandate of students in developing various skills of students, especially in improving social competence abilities in students. Social competence is the capacity to use cognitive and non-cognitive skills and talents to predict behavioral tendencies. This research was conducted at PAUD At TAdzkiroh using qualitative methods used to better understand the phenomena faced by research subjects. Data collection techniques include observation and interviews, while data analysis includes data reduction, data presentation, and conclusion/verification. Data reduction, data presentation, and conclusion/verification were used. Early childhood social competence is important for social, emotional, and cognitive development, and educational institutions need to guide extracurricular activities. Extracurricular activities are activities that take place outside of school or during school hours designed to encourage students, broaden their knowledge and skills, channel their talents and interests, and develop their personalities. They can also help children develop important social skills such as cooperation, communication, empathy, and problem-solving.Keywords: Education; Social Competence; Extracurricular